Does non-surgical periodontal treatment influence on rheumatoid arthritis? A systematic review and meta-analysis - Cleber Davi Del Rei Daltro Rosa; Jéssica Marcela de Luna Gomes; Sandra Lúcia Dantas de Moraes; Cleidiel Aparecido Araujo Lemos; Lurian Minatel; João Pedro Justino de Oliveira Limirio; Eduardo Piza Pellizzer (Elsevier, 2021)
Objective: The objective of this systematic review was to evaluate the efficacy of non-surgical periodontal therapy on rheumatoid arthritis activity. Material and methods: Articles published until April 2019 were electronically searched and screened using PubMed / MEDLINE, Scopus, and Cochrane databases according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines (PRISMA). This study was recorded in the international PROSPERO database (CRD42019132205). The PICO question (population, intervention, comparison, results) was: in adult patients with rheumatoid arthritis and periodontitis (P), does non-surgical periodontal treatment (I), as compared to no treatment (C), provides better outcomes in rheumatoid arthritis activity (O). Results: After searching the databases, seven articles were selected for qualitative and five for quantitative analysis. The total number of participants included was 292, with an average age of 50.5 years. All patients had rheumatoid arthritis and periodontal disease. Non-surgical periodontal treatment significantly reduced Disease Activity Score 28 (P = 0.004; I2 = 92%) and erythrocyte sedimentation rate (P = 0.01; I2 = 78%), but with no significant effect on C-reactive protein (P = 0.34; I2 = 92%). Conclusions: It can be concluded that non-surgical periodontal treatment can benefit patients with rheumatoid arthritis.